(untitled) (Modern education and development, 2025)
This article is devoted to the field of linguo-cultural studies of linguistics is a phraseology that expresses the concept of time in English and Uzbek languages units, i.e., idioms, linguistic and cultural aspects of proverbs are highlighted, English. It is discussed about the Uzbek language alternatives of the phraseological units of the language.